Ketidakpastian Hak Asuh Anak Akibat Perceraian Orangtua Muslim - Marpaung, Safriadi; Prasetiya, Nurul Huda; Marpaung, Watni (Kamaya: Jurnal Ilmu Agama, 2023)
Marriage is a form of sacred natural relationship between a man and a woman who are of appropriate age and mental stability with the aim of establishing a family, which will later contain a father, mother and children. Weddings are always synonymous with happiness and beauty, because they start with a sense of joy and sometimes glamor at the event. Not all marriages have a happy ending. Sometimes it will end in divorce. Through qualitative research methods with descriptive analysis. The approach taken is a phenomenological approach because researchers see based on phenomena that occur in the field plus in-depth interviews with informants, the divorce that occurs will have an effect on children regarding custody. A child's parenting style that is used to both parents will affect his psychology mentally and spiritually when he switches to one parent. The research results show that the case is a divorce between the plaintiff who works as a civil servant and the defendant who is a housewife. The reason the plaintiff rejected the defendant was because the defendant liked to fight. If divorce is the final solution to marriage, it is sufficient that it be between the ex-husband and wife. But that does not apply to the process of raising children, including their psychological development, it is good for whoever the child's custody falls to, but it is good that custody is in accordance with the applicable legal rules and regulations, because they are still the parents of their children. Proper child care will shape the child's good character.